Drag reduction of turbulent boundary layers by travelling and non-travelling waves of spanwise wall oscillations - Skote, Martin (MDPI, 2022)
Turbulence control in the form of a streamwise travelling wave of transverse wall motion was studied numerically by employing direct numerical simulations (DNS). Both total and phase averaging were utilised to examine the statistical behaviour of the turbulence affected by the wall forcing, with a focus on the skin friction. Comparison with results from pure temporal and spatial wall forcing are conducted, and a compilation of data is used to explore analogies with drag-reduced channel flow.
Keywords: turbulent skin friction reduction; direct numerical simulation; oscillating wall